THE OLD FASHIONED RELIGIOUS IMPERIALISM DEPICTED IN TOER’S ARUS BALIK: CRITICAL APPROACH ANALYSIS - Tirmidi, Tirmidi; Annisa, Nabila (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to describe and examine how colonialism is disguised in religious imperialism, meaning religion is used as a tool to carry out imperialism, in the historical setting of the early Islamic Kingdom of Demak, and colonization by the Portuguese in the archipelago. The study was conducted in two stages, namely to reveal how the theme is displayed in each part of the story, and the next stage is to reveal the key mechanisms in the practice of religious imperialism in the past. For the first objective, the approach used is the construction of story grammar offered by Mandler and Johnson, and for the second objective the researcher uses intertextual analysis from Gee. The results of the study illustrate that religious imperialism can be found in every part of the story: the setting, development and ending of the story. For the second objective, it was found that the key mechanisms of religious imperialism are religious conversion as a political tool, missionary or preacher activities and cultural domination, religious justification for colonial rule, and institutional control over religious practices.